Experimental study of heat transfer and pressure drop characteristics of microtube condenser using R134a. Issue 1 (31st December 2022) - Vinoth, R.; Sachuthananthan, B.
Abstract : The condensation heat transfer coefficient and the pressure drop were investigated experimentally and numerically in a microtube condenser using R134a. The microtube condenser comprises of trapezoidal oblique finned microchannel at the top and rectangular fins at the bottom of the tube. Water and air are used as cooling fluids on both sides of the microtube condenser. The experimental setup is validated initially with the existing work of Shah. The condensations effect included the vapour quality and mass flux ranging from 0.25 kg/m 2 s to 0.9, 99 to 468 kg/m 2 s, respectively. The results indicate that the condensation heat transfer coefficient and pressure drop enhance with mass flux and vapour quality. The experimental and numerical results are compared with existing experimental work. The microtube condenser enhances the heat transfer coefficient to 22.4% and a pressure drop of 5.6% more than the existing model. The heat transfer coefficient and pressure drop obtained from the numerical study is in superior agreement with the experimental results.